2001
DOI: 10.1086/321281
|View full text |Cite
|
Sign up to set email alerts
|

A Genome Screen of Families with Multiple Cases of Prostate Cancer: Evidence of Genetic Heterogeneity

Abstract: We conducted a genomewide screen for prostate cancer-susceptibility genes on the basis of data from 98 families from the United States and Canada that had three or more verified diagnoses of prostate cancer among first- and second-degree relatives. We found a statistically significant excess of markers for which affected relatives exhibited modest amounts of excess allele-sharing; however, no single chromosomal region contained markers with excess allele-sharing of sufficient magnitude to indicate unequivocal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 57 publications
4
41
0
Order By: Relevance
“…Interestingly, the location of a linkage signal at f80 cM on chromosome 3 reported in the current study corresponds to smaller peaks in the same region in genome-wide scans that were based on families ascertained in a similar way to ours (31,44). Minor peaks in the same region are also evident in one genomewide scan based on hereditary prostate cancer families (43). Our stronger linkage signal was likely the result of location of markers quite close to the candidate region, a consequence of the candidate gene approach we used, together with the probable reduction of locus heterogeneity achieved by testing linkage in the subset of multiple-affected siblings.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Interestingly, the location of a linkage signal at f80 cM on chromosome 3 reported in the current study corresponds to smaller peaks in the same region in genome-wide scans that were based on families ascertained in a similar way to ours (31,44). Minor peaks in the same region are also evident in one genomewide scan based on hereditary prostate cancer families (43). Our stronger linkage signal was likely the result of location of markers quite close to the candidate region, a consequence of the candidate gene approach we used, together with the probable reduction of locus heterogeneity achieved by testing linkage in the subset of multiple-affected siblings.…”
Section: Discussionsupporting
confidence: 81%
“…The chromosome 3 region bearing the FHIT gene has not been reported in previous genome-wide linkage scans, probably for a variety of reasons. Most previous studies used hereditary prostate cancer families that ascertained families with three or more cases among first-or second-degree relatives (40)(41)(42)(43), resulting in a tendency toward vertical transmission, with a higher probability of fathers being affected-a major characteristic of dominant traits (38). Interestingly, the location of a linkage signal at f80 cM on chromosome 3 reported in the current study corresponds to smaller peaks in the same region in genome-wide scans that were based on families ascertained in a similar way to ours (31,44).…”
Section: Discussionmentioning
confidence: 99%
“…A role for the host immune and inflammatory responses in the development of prostate cancer by implicating proliferative inflammatory atrophy of cells in the prostate gland in tumorigenesis has been proposed (3). Gene expression studies show MIC-1 overexpression in prostate cancer (4)(5)(6), whereas genomewide scans of multiple-case families provide evidence for linkage of the chromosomal region surrounding MIC-1 to prostate cancer (7,8). More recently, serum MIC-1 combined with prostate-specific antigen has been shown to improve the specificity of prostate cancer diagnosis (9).…”
Section: Introductionmentioning
confidence: 99%
“…Over-expression of AMACR may increase the risk of prostate cancer, because its expression is increased in premalignant lesions (prostatic intraepithelial neoplasia) [3,5]. Furthermore, epidemiologic, genetic and laboratory studies have pointed to the importance of AMACR in prostate cancer [26,27]. Genome-wide scans of linkage in hereditary prostate cancer families have demonstrated that the chromosomal region for AMACR (5p13) is the location of a prostate cancer susceptibility gene [9,10] and AMACR gene sequence variants (polymorphisms) have been shown to co-segregate with cancer of the prostate in families with hereditary prostate cancer [7].…”
Section: Introductionmentioning
confidence: 99%